Immunological loss-of-function due to genetic gain-of-function in humans: autosomal dominance of the third kind. (February 2015) - Boisson, Bertrand; Quartier, Pierre; Casanova, Jean-Laurent
Highlights: Gain-of-function mutations can cause autosomal dominant inborn errors of immunity. These disorders are increasingly recognized and often due to de novo germline mutations. They underlie various combinations of infection, cancer, allergy, autoimmunity, or autoinflammation. Abstract : All the human primary immunodeficiencies (PIDs) recognized as such in the 1950s were Mendelian traits and, whether autosomal or X-linked, displayed recessive inheritance. The first autosomal dominant (AD) PID, hereditary angioedema, was recognized in 1963. However, since the first identification of autosomal recessive (AR), X-linked recessive (XR) and AD PID-causing genes in 1985 ( ADA ; severe combined immunodeficiency), 1986 ( CYBB, chronic granulomatous disease) and 1989 ( SERPING1 ; hereditary angioedema), respectively, the number of genetically defined AD PIDs has increased more rapidly than that of any other type of PID. AD PIDs now account for 61 of the 260 known conditions (23%). All known AR PIDs are caused by alleles with some loss-of-function (LOF). A single XR PID is caused by gain-of-function (GOF) mutations (WASP-related neutropenia, 2001). In contrast, only 44 of 61 AD defects are caused by LOF alleles, which exert dominance by haploinsufficiency or negative dominance. Since 2003, up to 17 AD disorders of the third kind, due to GOF alleles, have been described. Remarkably, six of the 17 genes concerned also harbor monoallelic ( STAT3 ), biallelic ( C3, CFB, CARD11, PIK3R1 ) or both monoallelic and biallelic ( STAT1 ) LOF alleles in patients with other clinical phenotypes. Most heterozygous GOF alleles result in auto-inflammation, auto-immunity, or both, with a wide range of immunological and clinical forms. Some also underlie infections and, fewer, allergies, by impairing or enhancing immunity to non-self. Malignancies are also rare. The enormous diversity of immunological and clinical phenotypes is thought provoking and mirrors the diversity and pleiotropy of the underlying genotypes. These experiments of nature provide a unique insight into the quantitative regulation of human immunity.